PENERAPAN MODEL PEMBELAJARAN EXAMPLE NON-EXAMPLE DENGAN MEDIA GAME EDUKASI QUIZIZ DALAM MENINGKATKAN HASIL BELAJAR SISWA - Cynthia Marsela; Mona Mahyuni Hutagaol; Aslina Br Ginting; Junita Safitri; Lutfi Afis; Naomi Sitorus; Shanty Stevania Pangaribuan; Marshinta Gokmauli Gultom (Journal of Natural Sciences, 2021)
This study aims to determine the increase in student learning outcomes after applying the Non-Example Example learning model with the Quiziz Educational Game media to improve student learning outcomes in the seventh grade Solar System material at Maria Goretti Kabanjahe Private Junior High School. The no-example example learning model with quiziz game media is a learning strategy that uses pictures and videos as a medium to convey subject matter with the help of quiziz educational games as a medium in delivering the test instruments carried out. The subjects of this study amounted to 26 students. This non-example example method uses pretest and posttest actions in cycle I and cycle II, in order to improve student learning outcomes. Gradually in the pre-test, the average learning score was still 46.92 with a mastery percentage of 23.07%, followed by the first cycle, it was found that the student learning average was 48.46 and the percentage of completeness was 38.46%, there was a slight increase from before experiment was carried out. Then it was further improved in the second cycle, the researchers found an average learning score of 70.90 with a completeness percentage of 77.27%, it can be said that the improvement in student learning outcomes is getting better and increasing.